HUBUNGAN PAPARAN DEBU KAYU DENGAN KEJADIAN DERMATITIS KONTAK IRITAN PADA PEKERJA MEBEL PT X JEPARA - Farah Yudhistira Putri; Ari Suwondo; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Wood dust is an irritant substance and if it directly contact with the skin for a long time, it can cause workers exposed to the risk of irritant contact dermatitis. The purpose of this study was to analyze the relationship between irritant substances exposure with irritant contact dermatitis to sanding workers in PT X Jepara. The type and design of this study was an observational study using cross sectional approach. The instruments of this research are clinical examination by medical personnel, Personal Dust Sampler, questionnaires and observation.The population which used in this study were 139 with a sample of 60 sanding workers. The sampling technique that was use is proportionate stratified random sampling, and the data were analyzed using Chi Square test. The measurement results of respirable wood dust level showed the wood dust level exceed the Threshold Limit Value (TLV), which is 5 mg/m3. The result of this study indicates there are 21,7% of workers who had irritant contact dermatitis. Based on correlation test, researcher concluded that age is not associated with iritant contact dermatitis (p-value = 0,368), there is no correlation between years of service with the occurrence of irritant contact dermatitis (p-value = 0,182), there is no correlation between personal hygiene with the occurrence of irritant contact dermatitis (p-value = 0,689), and wood dust exposure is associated with iritant contact dermatitis (p-value = 0,005). Researcher suggested that workers need to wash their hands before and after working with hand soap, and the company need to educate workers the effect of wood dust exposure related to the occurrence of irritant contact dermatitis.